Camadas de crescimento de espécies arbóreas e arbustivas em um ecótono campo-floresta no sul do Brasil - Oliveira, Flávio de (Universidade do Vale do Rio dos Sinos, 2014)
In tropical regions, species of tree growth rings form in response to seasonal environmental factors that influence the activity of the vascular cambium. This study aimed to evaluate the existence and gross anatomical structure of the growth layers shrub and tree species in a field ecotone and forest of Southern Brazil. The work was developed in the Centro de Pesquisa e Conservação da Natureza (CPCN) Pró-Mata, in the municipality of São Francisco de Paula/RS, representing the forest-field ecotone occurring in the Araucaria Plateau region. Samples of 41 species were collected in the field and forest, which were extacted with the aid of a manual saw for extracting wood disc and using incremen borer, to remove small samples of cross sections. The samples were glued on a wood frame, sanded and polished in diferente particle size (80-600 grains) for better visualization of the anatomical characteristics of the wood. Images were captured in fifferent wood increases with aid câmera coupled with a stereomicroscope. The anatomical examination of wood taken from the plant enabled to view and characterize layers of growth of the species sudied. Amond the species analyzed, 19 showed distinct growth layers, 9 layers distinshable with difficulty and 13 layers with indistinct growth. For species that showed growth layers, most had demarcated the boundary layers of the thickness of the fibers. For species that showed growth layers, most há demarcated the boundary layers of the thickness of the fibers. Through anatomical study of wood samples analyzed, we found that the species representatives of the families Lauraceae and Fabaceae studied, forming layers of distinct growth good view, pointing to the region as a relevant potential for dendrochronological studies.
Keywords: Anatomia da madeira; Anéis de crescimento; Dendrocronologia; Wood anatomy; Growth rings; Dendrochronology; ACCNPQ::Ciências Biológicas::Biologia Geral